Government of Nagaland Draft Seventh Five Year Plan 1985-90 & Annual Plan 1985-86 Volume-II - Planning Commission (Planning Commission, 1984)
The establishment of this cell is considered necessary with two objectives, namely, to impart requisite training facilities to suitable youths on operation and maintenance of Computer equipment add secondly, to undertaken research and studies for application of computerised technology in specific area of works. With the sudden ushering in of Computer Technology in many spheres of activity, it is now absolutely necessary to prepare persons for proper operation and maintenance of Computer equipment. This will involve purchase, of appropriate equipment and facilities to be provided to the trainees, It will also be necessary to obtain the assistance and expert advice of Computer Scientists to identify areas for introduction of Computer Technology. The amount proposed for this is Rs.18.00 lakhs during the Five Year Plan period and an amount of Rs.8,00 lakhs during the year 1985-86.
Draft Seventh Five Year Plan 1985-90 & Annual Plan 1985-86 Volume-II
Government of Nagaland